1ISG-007 New cancer drug approvals in Portugal. (24th March 2020) - Alcobia, A; Soares, A
Abstract : Background and importance: In Portugal, all new drugs, after EMA approval, undergo a national health technology assessment process to decide their reimbursement status, by the SNS (Portuguese National Health System). Aim and objectives: The objective of this study was characterisation of the drug approval processes for cancer drugs by the INFARMED (Portuguese Regulatory Agency). Material and methods: The 10 latest drugs approved for different types of cancer were analysed, considering their therapeutic indication, type of economic analysis performed and efficacy outcome. Results: This analysis was performed in October 2019. The 10 latest cancer drugs approved (midostaurin, olaparib, brentuximab vedotin, pomalidomide, durvalumab, venetoclax, ixazomib, alectinib, atezolizumab and cabozantinib) are for use in refractory disease (60%), firstline treatment of metastatic disease (20%) and maintenance therapy in patients who have not progressed after firstline therapy (20%). A cost utility analysis was made for seven drugs, cost efficacy for two drugs and a cost minimisation analysis for two drugs (one of the drugs had two types of analysis as there were two different groups of patients). The efficacy outcome considered was overall survival in 60% and progression free survival in 30%. One evaluation considered overall response. The average HR for the efficacy outcome versus comparators was 0.74 for firstline or refractory disease therapies and 0.42 for drugs used in maintenance therapy when patients had not progressed after firstline therapy. Conclusion and relevance: The health technology assessment processes analysed were heterogeneous. Drug approvals must be balanced between clinical trials and real world evidence. For innovative drugs, clinical trial extensions must be published promptly after efficacy outcome modifications, leading to review of the reimbursement evaluations. References and/or acknowledgements: No conflict of interest.